Análise comparativa do metaboloma e proteoma de folhas de milho na aclimatação à salinidade induzida pelo pré-tratamento com H2O2 - Araújo, Gyedre dos Santos (2021)
Salinity is one of the major limiting factors crop productivity, it restricts plant growth and development, affecting almost all physiological, morphological, biochemical and molecular characteristics of plants. Thus, acclimation to salt stress is essential for survival and reproduction under this adverse condition. The use of hydrogen peroxide (H2O2) foliar pretreatment at low concentrations can attenuate the deleterious effects of salt stress and thus contribute to plant acclimation to such conditions. However, the mechanisms involved in the photosynthetic efficiency and the metabolites and proteins regulation of H2O2 pretreated maize plants under salinity are not fully understood. This study was designed in order to test the hypothesis that the use of H2O2 pretreatment mitigates the harmful effects of salinity on photosynthetic machinery by positively affecting the modulation of metabolites and proteins involved with salt tolerance. Therefore, two experiments were conducted with maize plants of genotype BR 5011, considered sensitive to salinity, pretreated with 10 mM H2O2 and then stressed with 80 mM NaCl under greenhouse conditions. In the first experiment; which aimed to analyze the photosynthetic efficiency, the structural integrity of chloroplasts and metabolites regulation of maize plants; was observed that salinity drastically affected the gas exchange parameters, maximum quantum efficiency (Fv/Fm) of photosystem II and chlorophyll b and total contents. In addition, NaCl-stress increased the reactive oxygen species (H2O2 and ·O2-) contents, caused structural damage to chloroplasts and promoted disturbances in the metabolite set of maize plants when compared to control conditions. However, our results suggest that H2O2-pretreated plants improve photosynthetic performance by avoiding salinity-induced excess energy, thus inducing increases in Fv/Fm, non-photochemical quenching (NPQ) and electron transport rate (ETR) values. In parallel, there was maintenance of thylakoids stacking, reduction in H2O2 and ·O2- contents and positive modulation of metabolites, mainly sugars and amino acids, which contributed to the maintenance of osmotic balance and reduction of oxidative stress. The second experiment aimed to relate growth analysis and ion accumulation (Na+ and K+) with changes in the proteomic profiling of maize plants. The imposed salt stress significantly affected the growth parameters, as well as increased the Na+/K+ ratio in leaves and promoted negative alterations in leaf proteome. In contrast, the use of H2O2 pretreatment positively influenced the phenotypic appearance in plants under salinity, confirmed by improved growth analyzes and reduced Na+ ion foliar contents. Additionally, there was regulation of important proteins that participate in metabolic pathways related to salt stress tolerance. In conclusion, these observations reveal that H2O2 pretreatment activates mechanisms involved in the positive modulation of crucial metabolites and proteins, which alleviates the harmful effects of salinity on photosynthetic machinery of the maize plants and increases the tolerance to salt stress